The Existence of Ludruk Show Behind The Popular Art Industry - Heny Purnomo (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2021)
The presence of popular art is described by the rapid growth anddevelopment of television medium influence the life of performingarts and the production activityin the show. Covid-19 and postpandemic activity also have an impact on art performance. Thecreative activity of traditional theater community are stagnating now,so that affecting the existence of show and leaving many problems.The development of popular art in ludruk show as a traditional theaterhas created a transformation of space and time as well as the aestheticvalue in it. When the institution as a "patron" no longer synergizeswith the art community, there is a clash of artistic process. Aestheticvalue present through the artistic process is used to get economicvalue only, in the end "beauty" is often interpreted as something thatonly produces commercial profit. Live ludruk show is difficult to findnow, and many events are often commodified into show. Televisionmedium, which grows rapidly and never leaves idle time, it hasinfluence the growth of entertainment industry which is orientedtoward commodity and financial gain. Gradually, the audieneces ofthe people traditional theater begin to decrease, and this socialphenomenon also gives an impact on the behavior of the audiencesand the existence of traditional theater show on the stage, so that thisissue is encouraging and interesting to be analyzed in a research.This study wants to describe the supporting aspect, form of change,and the existence of traditional theater show in the context of popularart industry.In analyzing the result, the theory of popular art industryis used supporting by the concept of dramaturgy by Guffman andother concepts as well as the result of interview on the spot. This studyusesqualitative descriptive method and popular art approach, itfocuses on data collection technique, namely; observation, interview,literature study, documentation, and triangulation as data validation.The target of the study is to provide information to academics.